2015
DOI: 10.1007/s40520-015-0442-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of walking speed with sagittal spinal alignment, muscle thickness, and echo intensity of lumbar back muscles in middle-aged and elderly women

Abstract: Background Age-related change of spinal alignment in the standing position is known to be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
0
15
1
2
Order By: Relevance
“…Trunk muscle balance with predominance of extensor over flexor muscles is associated with better physical capacity 41) and less back pain 31) . Masaki et al reported that maximal walking speed was negatively associated with the thickness of lumbar erector spinae muscles in middle-aged and elderly women 42) . Some authors have recently reported that the ratios of trunk flexion to extension in healthy untrained adults were usually lower than those in athletes 43) , suggesting that a superiority of trunk-extensor to flexor strength is associated with high performance even in the healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…Trunk muscle balance with predominance of extensor over flexor muscles is associated with better physical capacity 41) and less back pain 31) . Masaki et al reported that maximal walking speed was negatively associated with the thickness of lumbar erector spinae muscles in middle-aged and elderly women 42) . Some authors have recently reported that the ratios of trunk flexion to extension in healthy untrained adults were usually lower than those in athletes 43) , suggesting that a superiority of trunk-extensor to flexor strength is associated with high performance even in the healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cross-sectional area of both ESM and PMM did not recover to the point before admission until approximately one month after discharge, suggesting a possibility that patients had problems in their ADL. The reduction in thickness of lumbar and spinal muscle leads to decreased walking speed [13], and dysfunction of the PMM can be a cause of falls [11]. It is also reported that muscle strength of individuals in their 70s and 80s decreases by 20-40% compared to that of younger individuals, and 30% of those in their 60s may suffer from sarcopenia [14].…”
Section: Discussionmentioning
confidence: 99%
“…Adjusting the focus to the muscle ROI optimizes the image by increasing the spatial resolution for a specific area. Although this approach has been previously used for measuring EI estimates of muscle quality (Fukumoto et al 2012b;Masaki et al 2016;Taniguchi et al 2017), most often, focus position is not specified in the literature. The confounding effect of fat thickness is different between sonograms obtained with a fixed focus position (Figure 2A) and sonograms obtained with the focus adjusted to the ROI position within the sonogram ( Figure 2B).…”
Section: <<< Figure 2 >>>mentioning
confidence: 99%